Transformasi Perpustakaan Sekolah dalam Meningkatkan Minat Baca Siswa di SMA Negeri 6 Padang - Gusher, Femilia; Primadesi, Yona (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the transformation of the school library in increasing students 'interest in SMA 6 Padang, the problem to be disclosed are: (1) how to transform a collection of libraries in enhancing students' interest; (2) how the transformation of library facilities in enhancing students' interest; (3) how the transformation of librarians in improving students' interest. Based on the data gathered thus concluded that: (1) the amount of the collection is not in accordance with standards established by the National Library. Type collections of the library SMAN 6 Padang not meet the needs of students; (2) the existing facilities in the library SMAN 6 Padang is incomplete and limited; (3) The library staff library SMAN 6 Padang yet have the skills and extensive knowledge in the field of library management. Thus, the school SMAN 6 Padang should complete the collection in accordance with the needs of students at the same facilities and infrastructure and librarians in order to further improve performance in processing rapidly growing library that library. Keywords: transformation; interest in reading